Crystallization-Driven Supramolecular Gelation of Poly(vinyl alcohol) by a Small Catechol Derivative - Bonafe Allende, Juan Cruz (2022)
Catechol-containing molecules have been recognized as versatile building blocks for polymer structures with tailor-made functional properties. While catechol chemistry via metal-ligand coordination, boronate complexation, and oxidation-driven covalent bonds has been well examined in the past, the hydrogen bonding ability of these intriguing molecules has been dismissed. In this research, we investigated the gelation of poly(vinyl alcohol) (PVA) triggered by the crystallization of a 3,4-dihydroxy-catechol in water. Strong hydrogen bond interactions between PVA and catechol groups afforded supramolecular hydrogels with near-covalent elastic moduli, yet dynamic, exhibiting reversible gel-to-sol phase transitions around 50-60 °C. We studied the impact of the catechol derivative concentration on the gelation kinetics and physicochemical properties of these dynamic materials. Isothermal experiments revealed that heterogeneous crystallization governs the gelation kinetics. Moreover, because of the quasi-permanent cross-links within the supramolecular polymer network, these hydrogels benefit from ultrastretchability (∼600%) and high toughness (900 kJ·m-3). Our gelation approach is expected to expand the toolbox of catechol chemistry, opening up new avenues in designing dynamic soft materials with facile control over the phase transition, mechanics, and viscoelastic properties.